DANCES OF SOUTHERN AFRICA. Produced and filmed by Gei Zantzinger, edited Conley Benfield, sound Ruth Zantzinger. 16 mm. colour, 53 minutes, commentary Dr. Hugh Tracey, interview with Andrew Tracey. Distributed through Pennsylvania State Psychological Cinema Register, Audio-Visual Department - Nahumck, Nadia Chilkovsky (International Library of African Music, 1973)
pages: 102
Keywords: African Music